MicroRNAs expression profile of gefitinib resistant non-small cell lung cancer HCC827 cells - Quan, Duong Hong; Seong, Yeon-Sun (Academia Journal of Biology, 2015)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) such as gefitinib and erlotinib are promising therapies for patients with non-small-cell lung cancer (NSCLC). Patients with somatic activating mutations in the EGFR gene have dramatic response initially; however, these patients eventually develop resistance to these TKIs. Subsequent studies found that a secondary mutation in the EGFR gene (T790M mutation) and amplification of the c-MET could be the two main resistance mechanism involved. Other mechanisms are still unknown. Recently, MicroRNAs (miRNAs) have been identified as important posttranscriptional regulators which are known in the regulation of gene expression for cell development, cell proliferation, radiotherapy and chemotherapy resistance and apoptotic cell death. The aim of this study was to investigate miRNA expression profiles involved in the development of gefitinib resistance in NSCLC. Here, miRNA microarray assay was employed to identify miRNA expression profiles in gefitinib-resistant HCC827 cells (HCC827/GR) and parental HCC827 cells (HCC827/P). The comparison of miRNA expression between HCC827/GR and HCC827/P cell lines identified the differential expression of sixty-five miRNAs with eight significantly upregulated miRNAs (miRNA-198, miR-202, miR-210, miRNA-214, miR-22, miR-27a, miR-296-3p and miR-208b) and fourteen greatly downregulated miRNAs (miR-135b, miR-141, miR-145, miR-153, miR-181c, miR-181d, miR-188-3p, miR-197, miR-200c, miR-206-3, miR-215, miR-216a, miR-296-5p and miR-30a). The investigation of miRNA expression profiles in HCC827/GR cells could provide a better understanding of mechanisms involved in gefitinib resistance or sensitivity which would be helpful to develop novel strategies to overcome gefitinib resistance of patients with NSCLC.